Comparative analysis of workforce absenteeism due to medical reasons and its relation with risks in the work environment. - Bustamante Cataño, Adriana Maria
Introduction: Medically absenteeism is one of the most important indicators in organizations, as it affects multiple dimensions and directly impacts productivity, while also reflecting the health conditions of the workforce. Objective: To analyze medically absenteeism and identify its relationship with workplace risks in an education sector company in the department of Antioquia, Colombia, by reviewing the historical records of work-related disabilities from 2020 to 2024. Methods: A comparative descriptive study was conducted by reviewing 1,794 disability claims corresponding to 1,131 employees. Diagnoses were compared according to the International Classification of Diseases (ICD-11) and their relationship to occupational risks. Results: A relationship was found between medical absenteeism and occupational hazards, as 73% of the four-year absences (10,205 days) may be associated with workplace hazards. These results need to be compared with other studies and internal organizational measurements, considering the multifactorial etiology of absenteeism. Conclusion: Comparative descriptive studies make an important contribution to the review of historical data, enabling data-driven actions that allow organizations to identify the reasons for medical absenteeism and implement specific strategies to reduce it.